Position paper on ethical, legal and social challenges linked to audio- and video-based AAL solutions - Alin Ake-Kob; Slavisa Aleksic; Zoltán Alexin; Aurelija Blaževičienė; Anto Čartolovni; Liane Colonna; Carina Dantas; Anton Fedosov; Eduard Fosch-Villaronga; Francisco Florez-Revuelta; Zhicheng He; Aleksandar Jevremović; et al. (University of Alicante, 2022)
In this position paper, we have used Alan Cooper's persona technique to illustrate the utility of audio- and video-based AAL technologies. Therefore, two primary examples of potential audio- and video-based AAL users, Anna and Irakli, serve as reference points for describing salient ethical, legal and social challenges related to use of AAL. These challenges are presented on three levels: individual, societal, and regulatory. For each challenge, a set of policy recommendations is suggested.
Keywords: J14; L86; M14; O18; O33; 330; ethics; privacy; computer vision; audio processing; active assisted living; active ageing; silver economy